Mangabeiras of the Delta: production scenario science in physical geography piauiense in local events (PerCursos, 2022)
The state of Piauí has a rich Geodiversity in natural environments subject to numerous investigations in various areas of knowledge, especially in the field of Physical Geography. Thus, there is a considerable number of studies that have addressed this theme assisting thus in scientific advancement and discovery of new local realities, before that, the present study aims to carry out a theoretical research, methodological and spatial studies in interpretation of Physical Geography Piauí from local events held between 2013 and 2018. Characterized as State of Art, this study examined 240 papers published in the annals of 11 scientific events, in qualitative and quantitative approach and using QGIS software (3:16, Hannover version) spatial distribution of studies in Geographic Regions Intermediate (6) and Immediate (19). The results achieved that among the 11 categories/themes studies, the highlights were those on Social and Environmental Impacts, Geography and Physical Education and Other, 55, 39 and 35 studies, respectively. Similarly, the tangent to the methodological procedures, the adoption of test Bibliographic/Documentary and field studies were consensus applications 240 and 135, respectively, with strong theoretical load systemic approach. In the context of the spatial distribution of applied studies, these are concentrated largely in the North Central Piauiense portion, especially in Intermediary and Immediate Geographic Regions Teresina and Parnaíba, as well as the lack of studies in Immediate Geographic Regions Oeiras, Simplicio Mendes and Corrente, concluding there is a very uneven distribution of studies over certain regions, even if rich in analytical possibilities.
Keywords: physical geography; Piauí; local events; categories and themes; spatial distribution